Pemanfaatan Limbah Kotoran Sapi dan Molase Kulit Pisang Sebagai Efektifitas Produksi Biogas di Desa Daeo Kabupaten Pulau Morotai - Aja, Muhammad Fahmi; Saleh, Hasrul; Siti Hanian Bilo (Jurnal Serambi Engineering, 2025)
The community's dependence on kerosene remains a major issue, especially in disadvantaged, frontier, and outermost (3T) areas such as Morotai Island Regency. This study focuses on the utilisation of fresh cow dung waste combined with banana peel molasses as raw materials for biogas production. The research methods used were quantitative descriptive and experimental with trials on three digester designs. Based on the results of the study, the three digester designs showed significant differences, where RD1 was less than optimal because the low pH (6) caused unstable CH₄ production, 0 psi pressure, (CO₂, CO = 0), RD2 was the best design with neutral pH (7), stable mesophilic temperature (25–31 °C), high pressure (34 psi), and consistent CH₄ production increasing to 10,100 ppm, while RD3 was still able to produce fairly high CH₄ (8,731 ppm) despite relatively acidic pH. Regression analysis shows that in RD1, pH greatly affects CH₄ (R² = 0.899), while in RD2 and RD3, temperature is the dominant factor (R² > 0.997) in increasing methane production. In general, neutral pH and mesophilic temperature conditions proved to be most conducive to methanogenic bacterial activity, with RD2 as the most optimal digester design producing high-quality biogas with a neutral pH of 7, temperature of 31°C and pressure of 34 psi, and CH₄ consistently increasing to 10,100 ppm.